16QAM Wireless Communication Model - Meenaakumari, M. (International Journal of Psychosocial Rehabilitation, 2018)
Software defined radio (SDR) has emerged as a priority theme of research since it will substitute for conventional implementation on wireless communication system. In this paper, a multi-standards SDR model is designed and implemented in FPGA form using Xilinx system generator technique. According to the under sampling theory which is used in this model, the received 70MHz carrier is sampled at 40MHz and the performance of the proposed model with different standards’ like GSM,OFDM, and WCDMA using 16QAM modem is produced attractive behavior with different channel effective and minimum BER. Therefore make develop on 3G of wireless and mobile systems more economical, effective and accelerate the transition from 3G to 4G of wireless systems.